PENGARUH PENAMBAHAN BELIMBING WULUH (Averrhoa bilimbi) TERHADAP DAYA TERIMA SELAI PEPAYA CALIFORNIA (Carica papaya) - Dewi Rochmatul Ummah; Hidayatun Muyasyaroh; Fitri Komala Sari; Nugrahani Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Jam is a semi-solid product made from sugar and fruit. California papaya has the potential to be developed into jam due to its abundant availability, sweet taste, soft texture, and pectin content, which aids in gel formation. Papayas have a short shelf life and spoil quickly, especially if California papayas remain unsold for too long due to their higher price compared to other varieties; therefore, they need to be processed into jam with the addition of bilimbi as a source of citric acid and to impart a distinctive flavor. One innovation to prevent papaya waste is to process it into jam by adding bilimbi as a source of citric acid and to provide a distinctive aroma and flavor. This study aims to determine the effect of adding bilimbi (Averrhoa bilimbi) on the acceptability of California papaya (Carica papaya) jam in terms of taste, aroma, color, and bilimbi fruit added. Data analysis was performed using the Kruskal-Wallis and Mann-Whitney tests, with results indicating that the addition of bilimbi had a significant effect on the acceptability of the color, aroma, and taste of California papaya jam, whereas it had no significant effect on consistency.